2014
DOI: 10.4161/cc.27769
|View full text |Cite
|
Sign up to set email alerts
|

Reconciliation of classification systems defining molecular subtypes of colorectal cancer

Abstract: Recently we published two independent studies describing novel gene expression-based classifications of colorectal cancer (CRC). Notably, each study stratified CRC into a different number of subtypes: one reported 3 subtypes, whereas the second highlighted 5. Given that each ascribed clinical significance, distinctive biology, and therapeutic prognosis to the different subtypes, we sought to reconcile this apparent incongruity in subtype stratification of CRC, and to interrelate the results. To do so, we each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 12 publications
4
59
0
5
Order By: Relevance
“…A close comparison between these two datasets has shown that the CCS2-MSI subgroup encompasses the inflammatory and goblet subtypes (44). According to the authors, these associations make sense also in light of previous studies (45), as MSI tumors are often associated with an inflammatory immune infiltrate and a mucinous phenotype (44).…”
Section: Discussionsupporting
confidence: 53%
“…A close comparison between these two datasets has shown that the CCS2-MSI subgroup encompasses the inflammatory and goblet subtypes (44). According to the authors, these associations make sense also in light of previous studies (45), as MSI tumors are often associated with an inflammatory immune infiltrate and a mucinous phenotype (44).…”
Section: Discussionsupporting
confidence: 53%
“…GPx2 levels are associated with metastasis formation, particularly in the aggressive CCS3 subtype, which has a primitive stem-like phenotype (22,45) and is relatively resistant to current systemic therapy (22). We therefore propose that therapeutically increasing ROS levels, either through targeting GPx2 or by other means, may be particularly effective in sensitizing the aggressive colon tumor subtype to chemotherapy and/or in reducing their propensity to form metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Se presenta en 15%-20% de CCR esporádicos y se le asocia a mal pronós-tico 13,14 . Debido a la heterogeneidad y complejidad de los tumores, diversos estudios han propuesto subgrupos moleculares de CCR basados en las 3 vías antes descritas [15][16][17][18][19] . Los esfuerzos en determinar el perfil molecular de CCR tienen como fin comprender mejor los mecanismos que determinan el comportamiento clínico de los diferentes tumores y, de esta manera, identificar biomarcadores que proporcionen información pronóstica precoz.…”
unclassified